2016
DOI: 10.17116/terarkh201688731-36
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of the promoter regions of the SOX7 and p15INK4b genes and Wnt signaling pathway antagonists in patients with acute myeloid leukemias

Abstract: AM of the p15NK4b and SOX7 genes and Wnt signaling pathway antagonists is detected in the majority of patients with AML, which allows hypomethylating agents to be recommended for the treatment of patients who cannot use intensive cytostatic therapy for different reasons. The detection of a large number of genes with the aberrant methylation status in most AML patients with myelodysplasia or a complex karyotype serves as the basis for initiating trials to evaluate the efficiency of a combination of 5-azacytidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The mutation and aberrant methylation in the promoter region of tumor suppressor genes, oncogenes, transcription factors and drug response genes could influence the gene expression and play important role in the tumorgenesis, tumor progression and response to treatment [2022]. However, the AKT1 mutation and the methylation profile in its promoter region and their role in breast cancer are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The mutation and aberrant methylation in the promoter region of tumor suppressor genes, oncogenes, transcription factors and drug response genes could influence the gene expression and play important role in the tumorgenesis, tumor progression and response to treatment [2022]. However, the AKT1 mutation and the methylation profile in its promoter region and their role in breast cancer are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, numerous studies have indicated that the pathogenesis of AML involves the abnormal activation of Wnt signaling pathway, which has a key role in extensive cellular processes of hematopoietic progenitor proliferation and differentiation. 12 14 Wnt signaling pathway comprises the canonical pathway with β-catenin and the non-canonical pathways involving calcium ions and planar cell polarity. 15 17 Growing evidence suggests that the Wnt signaling pathway plays an important role in normal HSCs maintenance, whereas nuclear β-catenin is a key molecule that mediates transcriptional activation of specific gene expression and is thought to have the most significance in cancer development.…”
Section: Introductionmentioning
confidence: 99%